Memorization and discussion methods effect on achievement and communication skills - Sukino Sukino; Sumin Sumin; Erwin Mahrus; Ahmad Salim; Imron Muttaqin; Triyo Supriyatno (Institute of Advanced Engineering and Science, 2024)
This study aimed to determine learning outcomes and discuss the effect of the combination of memorization and small group discussion methods on students’ achievement and communication skills. A quantitative method was applied in this study with a quasi-experimental design. The subject of this study is 60 students in Islamic Education, Faculty of Education and Teacher Training (FTIK) at the Pontianak State Institute for Islamic Studies, divided into a control and an experimental group. Data were collected through pre-test and post-test from the control and experimental groups and then analyzed using the independent samples t-test using statistical software JASP version 0.16.4. The findings revealed that there are differences between outcome learning and communication skills between the control group which only uses the small group discussion method and the experimental group which employs a combination of memorization and small group discussion methods in the course of developing Islamic Education material. The findings of this study confirm that combining the two methods, memorization, and small group discussion, is highly effective in improving learning achievement and communication skills at the student level. Further research is suggested to explore and determine other factors affecting learning outcomes and methods.